Simultaneous effects of nutritional and environmental factors on growth and flesh quality of Perca fluviatilis using a fractional factorial design study - Gardeur, Jean-Noel; Mathis, Nicolas; Kobilinsky, Andre; Brun-Bellut, Jean (Aquaculture, 2007)
Fractional factorial design is a practical approach for studying multiple factors, with a minimum of experimental units. The objective of this work was to study the simultaneous effects of nutritional and environmental factors on both growth and flesh quality of common perch (Perca fluviatilis), a new inland aquaculture species. This study sought answering the two following questions: (i) which combinations of factors allow improving growth, food efficiency, and technological, sensorial and nutritional qualities? (ii) is it possible to simultaneously improve growth performances and flesh quality? In a first experiment, twelve factors (7 nutritional and 5 environmental factors) were each tested at 2 levels in a fractional factorial design in 24 independent recirculating 500 L tanks. The best 4 combinations identified in this first experiment were then validated in a second experiment. The first phase of the multifactorial approach used here allowed revealing emergent information: i) there is a combination of factors that allows reducing both the heterogeneity of the production and the losses of nitrates and phosphates, while preserving good characteristics of growth and quality of fillets; ii) it is possible to improve the quality of the aquatic production system, without decreasing significantly growth efficiency; iii) the effect of a given factor, even such an important one like diet, temperature or target biomass, depends on the levels of the other rearing factor levels, thus the usual reference optimum used for a given factor has no meaning theoretically and can be questioned according to the levels of the other factors which act altogether on the functioning of the rearing system. The input factor combinations resulting in a significant enhancement of single output variables or several output variables were identified (e.g. improvement of feed efficiency, and/or fillet docosahexanoic acid content). Our results clearly demonstrate a strong interdependence of input factors into the animal rearing system, particularly between nutritional and environmental ones.